ANALISIS KESULITAN MEMBACA PERMULAAN PADA SISWA KELAS 2 SDN JABON BARAT TAHUN AJARAN 2024/2025 - Karisma Wati; Sudirman; Mansur Hakim (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to describe initial reading difficulties in class II students at SDN Jabon Barat and describe how to overcome initial reading difficulties in class II students at SDN Jabon Barat. This research is descriptive qualitative research. The subjects of this research were class II students at SDN Jabon Barat for the 2024/2025 academic year with a total of 26 students. Data collection techniques consist of observation, tes, interviews and documentation studies. Data analysis techniques use data reduction, data and presentation. The results of this research show that the initial reading difficulties experienced by class II students at SDN Jabon Barat are difficulty in recognizing letters, difficulty in recognizing vowels, consonants and diphthongs, difficulty in spelling letters and difficulty in reading simple sentences. The ways to overcome the initial reading difficulties experienced by class II students at SDN Jabon Barat are, giving more attention to students who experience difficulties in initial reading, increasing reading hours after teaching and learning activities, reading together, learning while playing and collaborating with the student's parents.